2006
DOI: 10.1038/sj.bjc.6603242
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synergistic cytotoxicity of gemcitabine and pemetrexed and pharmacogenetic evaluation of response to gemcitabine in bladder cancer patients

Abstract: The present study was performed to investigate the capability of gemcitabine and pemetrexed to synergistically interact with respect to cytotoxicity and apoptosis in T24 and J82 bladder cancer cells, and to establish a correlation between drug activity and gene expression of selected genes in tumour samples. The interaction between gemcitabine and pemetrexed was synergistic; indeed, pemetrexed favoured gemcitabine cytotoxicity by increasing cellular population in S-phase, reducing Akt phosphorylation as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 27 publications
(34 reference statements)
4
24
0
1
Order By: Relevance
“…Our findings are in agreement with several studies demonstrating a reduced Akt phosphorylation after exposure to the antimetabolite gemcitabine (Giovannetti et al, 2005;Bianco et al, 2006;Chun et al, 2006;Mey et al, 2006;Feng et al, 2007). In particular, Feng et al (2007) proposed a model of gemcitabine-induced apoptosis via EGFR degradation, explaining the possible mechanism by which a cytotoxic compound may affect EGFR and Akt signaling pathways.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings are in agreement with several studies demonstrating a reduced Akt phosphorylation after exposure to the antimetabolite gemcitabine (Giovannetti et al, 2005;Bianco et al, 2006;Chun et al, 2006;Mey et al, 2006;Feng et al, 2007). In particular, Feng et al (2007) proposed a model of gemcitabine-induced apoptosis via EGFR degradation, explaining the possible mechanism by which a cytotoxic compound may affect EGFR and Akt signaling pathways.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the combination of pemetrexed and erlotinib with the PI3K inhibitor LY294002 resulted in a synergistic interaction, suggesting that combinations of specific signal transduction inhibitors targeting different steps of EGFR-PI3K pathways may be a successful strategy against NSCLC. Because phospho-Akt regulates antiapoptotic mechanisms and previous in vitro studies showed that its down-regulation by pemetrexed correlated with the enhancement of gemcitabine-induced apoptosis and antitumor activity in lung and bladder cancer cells (Giovannetti et al, 2005;Mey et al, 2006), the reduction of pS-473Akt may explain the increased apoptosis found in the pemetrexed-erlotinib combination.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment in accordance with the characteristics of the pancreatic cancer cells is needed. Many studies have reported the effectiveness of combination treatment of anticancer drug and inhibitor or gene transduction (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). There is no treatment that is effective for all carcinomas with various characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…They also sequenced the entire DCK-encoding gene in 17 human pancreatic cancer cell lines and nine samples of cancer tissue from patients, but no mutations were identified. Mey et al (2006) administered gemcitabine intravesically to 12 patients with bladder cancer, and reported that the mean expression of mRNA in the tumours was significantly higher in patients who achieved a complete pathological response than in those who did not. On the other hand, Seve et al (2005) reported that immunohistochemical expression of DCK protein in tumours was not significantly correlated with the survival of NSCLC patients treated with gemcitabine-based chemotherapy.…”
Section: Deoxycytidine Kinasementioning
confidence: 99%